(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Introduction: Acute kidney injury (AKI) is an important clinical problem in sick neonate. In most patients, AKI accompanies with a predisposing factor such as sepsis, asphyxia and surgery. The aims of this study were to determine the incidence, associated contributing factors and short term outcome of AKI in hospitalized newborn infants. Materials and Methods: This prospective cohort study was done in Dhaka Shishu Hospital from March 2011 to September 2011. This study included 300 sick neonates admitted during the study period. AKI was defined when serum creatinine level >1.5 mg/dl and BUN was >20 mg/dl on two separate occasions at 24 hours apart. Oliguria was defined as urine output <1ml/kg/ hr. Medical records of those patients were reviewed and data were analyzed using SPSS software. Results: Fourteen babies (4.66%) out of 300 sick neonates had AKI, of whom 64.2% were male and 35.7% female. The term and preterm neonates were 71% and 29% respectively. While a normal birth weight was observed in 57% cases, 35% had low birth weight and 7.14% had very low birth weight. Sepsis was the most common (71%) association of AKI, followed by perinatal asphyxia (52%). All patients had more than one predisposing factors. Frequency of oliguric kidney injury was 57% and non-oliguric was 43%. Mortality among the hospitalized neonate with AKI was 21%. Conclusion: This study showed that in a tertiary care hospital AKI is not uncommon (4.66%) in neonatal care unit. It is associated with some preventable conditions such as sepsis, perinatal asphyxia and shock. Outcome is poor in sick neonates with AKI (21% mortality) in comparison to sick neonates without AKI (10.3%). J Bangladesh Coll Phys Surg 2017; 35(1): 20-23